A novel bisection method based algorithm to quantify interphase in epoxy alumina nanocomposites - Singh, Manohar; Rajendran, Vasantha Kumar; Pandey, Jeewan Chandra (Computational materials science, 2020)
Polymer nanocomposites (PNCs) are emerging materials for the future due to their superior material characteristics with respect to base polymer and composites formed with traditional micro sized fillers. Researchers are concordant in attributing the improved properties of PNCs to large proportion of polymer-filler interaction zone (or an interphase). However, literature is indeed scanty to characterize interphase in terms of its size and properties. To come into possession of fine-tuned material properties through optimal use of naofillers, characterization of interphase is necessary. In this work, we propose a novel algorithm to characterize interphase in terms of its permittivity and thickness. Epoxy resin (LY556) is used as base polymer and aluminum oxide (Al2O3, average particle size = 50 nm) is used as filler material. Filler particles are surface treated using silane. Dispersion of nano filler in polymer matrix is verified using scanning electron microscopy (SEM). Dielectric spectroscopic measurements are carried out to measure permittivity over a frequency range of 10-2 to 107 Hz. A finite element based numerical model is developed to estimate effective permittivity of composites for different values of assumed interphase parameters (i.e. thickness and permittivity). Bisection method based algorithm is devised to assign actual thickness and permittivity to interphase based on the best fit of experimental and simulated results.